Comparative Evaluation of Triphala, Aloe vera, and chlorhexidine mouthwash on gingivitis: A randomized controlled clinical trial - Gautami S Penmetsa; B Vivek; Arun P Bhupathi; P Sudha Rani; B V Subbareddy; M V Ramesh (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study was to assess the effectiveness of two herbal mouthwashes in comparison with Chlorhexidine mouthwash on gingivitis. Materials and Methods: This is a triple-blind randomized controlled clinical trial, where in 60 patients were randomly allocated into three study groups: Triphala mouthwash (Group A), Aloe vera mouthwash (Group B), and Chlorhexidine mouthwash (Group C). All groups were treated with scaling and asked to rinse with respective mouthwashes twice daily for 1 month. Clinical parameters such as plaque index (PI), gingival index (GI), and bleeding index (BI) were recorded at baseline, 15 days, and 30 days, respectively. Results: Our results suggested that Triphala group effectively demonstrated a higher reduction in GI and BI index scores compared to A. vera group (P ≤ 0.005) and the effect is equivocal to the reduction seen with Chlorhexidine group. However, no statistically significant difference was observed between the mouthwashes in reduction of PI scores (P > 0.005). Conclusion: The results of our study evidenced Triphala to be superior in the reduction of plaque, gingival inflammation, and bleeding compared to that of A. vera. However, the results of our study also indicated that Triphala was as effective as chlorhexidine mouthwash in its ability in reducing plaque accumulation, gingival inflammation, and bleeding. Furthermore, Triphala is relatively free of side effects compared to that of chlorhexidine.